PENGARUH ETOS KERJA TERHADAP KINERJA PEGAWAI PADA PEGAWAI KEMENTERIAN AGAMA PROVINSI SUMATERA SELATAN - Awalia Nabilla; Hidayat Ht; Muzaiyanah Muzaiyanah (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
This research seeks to elaborate on the work ethic of employees in an institution and the impact it has on their performance. The purpose of this study was to determine the effect of work ethic on employee performance in the regional office of the Ministry of Religion, South Sumatra province. This research is a field research (field research) with a quantitative approach. Data collection and survey techniques were carried out by distributing questionnaires. Furthermore, sampling was carried out by using non-probability sampling technique; saturated sampling, which is a sampling technique that makes the entire population as a sample totaling 44 people. Data were analyzed by Instrument Test (Validity and Reliability Test), Simple linear regression analysis, Basic assumption test and Hypothesis Test (t test and Determination Coefficient Test) using SPSS version 23 software tools. The results showed that there was an effect of work ethic on performance employee. It is proven that the R Square value in the table is 0.114 which indicates that the Employee Performance variable (Y) is influenced by the Work Ethics variable (X) of 11.4% and the remaining 88.6% is influenced by other factors not examined such as motivation and others.